French Registry on Acute ST-elevation and non ST-elevation Myocardial Infarction 2010. FAST-MI 2010. Issue 9 (20th April 2012) - Hanssen, Michel; Cottin, Yves; Khalife, Khalife; Hammer, Laure; Goldstein, Patrick; Puymirat, Etienne; Mulak, Geneviève; Drouet, Elodie; Pace, Benoit; Schultz, Eric; Bataille, Vincent; Ferrières, Jean; et al.
Abstract : Aim of FAST-MI 2010: To gather data on characteristics, management and outcomes of patients hospitalised for acute myocardial infarction (AMI) at the end of 2010 in France. Interventions: To provide cardiologists and health authorities national and regional data on AMI management every 5 years. Setting: Metropolitan France. 213 academic (n=38), community (n=110), army hospitals (n=2), private clinics (n=63), representing 76% of centres treating AMI patients. Inclusion from 1 October 2010. Population: Consecutive patients included during 1 month, with a possible extension of recruitment up to one additional month (132 centres); 4169 patients included over the entire recruitment period, 3079 during the first 31 days; 249 additional patients declining participation (5.6%). Startpoints: Consecutive adults with ST-elevation and non-ST-elevation AMI with symptom onset ≤48 h. Patients with AMI following cardiovascular procedures excluded. Data capture: Web-based collection of 385 items (demographic, medical, biologic, management data) recorded online from source files by external research technicians; case-record forms with automatic quality checks. Centralised biology in voluntary centres to collect DNA samples and serum. Long-term follow-up organised centrally with interrogation of municipal registry offices, patients' physicians, and direct contact with the patients. Data quality: Data management in Toulouse University. Statistical analyses: Université Paris Descartes, Université de Toulouse, Université Pierre et Marie Curie-Paris 06, Paris. Endpoints and linkages to other data: In-hospital events; cardiovascular events, hospital admissions and mortality during follow-up. Linkage with Institute for National Statistics. Access to data: Available for research to any participating clinician upon request to executive committee (fastmi2010@yahoo.fr ).